The Effect of Income Tax on Public Welfare in North Tugu - Nuramelia, Lia; Supraptiningsih, Joelianti Dwi; Mustika, Yana (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research examines the effect of income tax on public welfare in Tugu Utara Village, Koja District, North Jakarta. The main objective of the research is to analyze income tax on the welfare of residents in the region. This research applies a quantitative descriptive approach, collecting data through surveys and direct dialogue. Samples were selected by randomly purposive sampling, involving 47 respondents in Tugu Utara, North Jakarta. Data analysis uses a simple linear regression model. Research findings indicate the influence of income tax on public welfare in Tugu Utara, North Jalarta, North Jakarta. It is hoped that this research can become a valuable reference for subsequent studies.